Jordan : supporting stable development in a challenging region : a joint World Bank-Islamic Development Bank evaluation - Hassan, Fareed M. A.; Al-Saci, Djelloul; Islamic Development Bank.; World Bank. (Washington, D.C. : World Bank ; Jeddah, Saudi Arabia : Islamic Development Bank, 2004)
This evaluation, prepared in collaboration with the Islamic Development Bank, looks at the effectiveness of Bank assistance to Jordan during the 1990s, from three perspectives: an analysis of the Bank's services and products, development impact, and the contribution of the Bank and its development partners, to development outcomes.
At head of title: World Bank Operations Evaluation Department, Islamic Development Bank Operations Evaluation Office.
Includes bibliographical references.
oif 15/09/15
Loan
Keywords: Jordan -- Social conditions; Jordan -- Economic conditions